Future Challenges and Strategic Directions of Zakat Management in Indonesia’s National Legal System - Hendriko Arizal; Ahmad Iffan; Roni Efendi (Jurnal El-Thawalib, 2026)
Zakat plays an important role in supporting social welfare and poverty alleviation in Muslim societies. In Indonesia, zakat management has developed significantly following the enactment of Law Number 23 of 2011 concerning Zakat Management. Despite Indonesia’s large zakat potential, various legal, institutional, and technological challenges continue to hinder the optimization of zakat governance. This study aims to examine the future challenges and strategic directions of zakat management within Indonesia’s national legal system. The research employs normative legal research using statutory, conceptual, and limited comparative approaches. The findings indicate that Indonesia has established a relatively strong legal framework through BAZNAS, LAZ, and UPZ institutions. However, several problems remain unresolved, including overlapping institutional authority, weak supervision mechanisms, disparities in institutional capacity, limited public participation, and the gap between zakat potential and actual collection. In addition, digital transformation has introduced new opportunities as well as challenges related to transparency, accountability, cybersecurity, and digital governance. Therefore, strengthening zakat management in Indonesia requires institutional harmonization, adaptive legal reform, stronger digital governance, and better integration between Islamic social finance and national public policy in order to support sustainable social welfare and economic empowerment